1997
DOI: 10.1164/ajrccm.155.5.9154891
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte growth factor increases transalveolar sodium reabsorption in normal and injured rat lungs.

Abstract: Keratinocyte growth factor (KGF) prevents alpha-naphthylthiourea (ANTU)-induced permeability edema ex vivo. To explore the mechanisms in this involved effect, we administered KGF (5 mg/kg, intratracheally) 48 h prior to ANTU (50 mg/kg, intraperitoneally). Several groups were studied: phosphate-buffered saline/dimethylsulfoxide (PBS/DMSO) (vehicles), PBS/ANTU, and KGF/ANTU. At 90 min after ANTU injection the lungs were removed, ventilated, and perfused ex vivo for 180 min. Quantification of fluorescein isothioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
70
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 0 publications
5
70
1
Order By: Relevance
“…The protective effect of KGF is multifactorial. The current authors have shown, in a-naphthylthiourea-induced lung injury, a potentiation of alveolar fluid clearance through sodium-potassium-adenosine triphosphatase stimulation [14]. In Pseudomonas aeruginosa pneumonia, KGF restored lung liquid clearance related to an improvement of the endothelial barrier [15].…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…The protective effect of KGF is multifactorial. The current authors have shown, in a-naphthylthiourea-induced lung injury, a potentiation of alveolar fluid clearance through sodium-potassium-adenosine triphosphatase stimulation [14]. In Pseudomonas aeruginosa pneumonia, KGF restored lung liquid clearance related to an improvement of the endothelial barrier [15].…”
mentioning
confidence: 64%
“…KGF has been demonstrated to be a potent mitogen of alveolar epithelial type II cells in the lung, and also of bronchial epithelial cells in vitro and in vivo [10,11,29]. The protective effect of KGF has been demonstrated in different situations, including the prevention of cell loss but also the repair of the epithelium after injury [14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5B). Because previous studies demonstrated that KGF increased ␣ENaC expression at the mRNA level (35,36), we tested the effect of MSCs on both trafficking of ENaC subunits to the apical surface using biotinylation and on total cellular protein levels in the cultured alveolar type II cells injured with cytomix. Cytomix reduced both the total cellular level and the apical membrane expression of ␣ENaC by 41% and 50%, respectively, at 24 h in primary cultures of human alveolar epithelial type II cells.…”
Section: Effect Of Msc On Net Fluid Transport In Primary Cultures Of mentioning
confidence: 99%
“…In adult respiratory distress syndrome animal models, the administration of KGF before injurious ventilation has been shown to protect the lung (6,7). In addition to its role as an epithelial cell mitogen, KGF also has been shown to increase the expression of surfactant proteins and improve alveolar fluid clearance (8,9).…”
mentioning
confidence: 99%